Genetic variability to improve yield and resistance to bacterial leaf blight in rice - Singh, AK; Singh, RK; Kumar, Sunil; Arya, M; Singh, PK (Bangladesh Journal of Botany, 2018)
One hundred F2 and F3 single plant progenies along with their parents and the infector rows were evaluated for 13 quantitative traits to assess the genetic variability, heritability, associations and estimation of number of genes for bacterial leaf blight resistance and yield related traits. In both F2 and F3, a wide range of variability was present for all the traits, indicating considerable scope for selection. High heritability accompanied with high genetic advance was observed for plant height, panicle length, panicle weight, number of effective tillers per plant and grain yield per plant. Positive and significant correlation were observed between grain yield per plant with days to 50% flowering, plant height, panicle length, panicle weight, number of effective tillers per plant, test weight and flag leaf length in either one of the generation or in combination of both F2 and F3. Path-coefficients analysis showed that plant height, panicle length and test weight had high direct positive effect in both the F2 and F3. The estimated number of gene(s) in the segregating generations for bacterial leaf blight was 2.14 in the F2 and 0.92 in the F3 revealed that two genes were involved in the inheritance of resistance to bacterial leaf blight in F2, while only one gene in F3 due to dominance effect.